2011
DOI: 10.5840/beq201121436
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Authentic Leadership, Moral Courage, and Ethical and Pro-Social Behaviors

Abstract: ABSTRACT:Organizations constitute morally-complex environments, requiring organization members to possess levels of moral courage sufficient to promote their ethical action, while refraining from unethical actions when faced with temptations or pressures. Using a sample drawn from a military context, we explored the antecedents and consequences of moral courage. Results from this four-month field study demonstrated that authentic leadership was positively related to followers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
319
7
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(349 citation statements)
references
References 67 publications
(162 reference statements)
11
319
7
12
Order By: Relevance
“…However, one commonality in notions of leadership is that they encompass a perspective on 'the other', whether this is in terms of employee followership, or, a wider stakeholder perspective. Indeed, for the purposes of our micro-and meso-levels of analysis of CSR leadership, the psychological concepts of prosocial (Penner et al 2005) and, conversely, antisocial behaviour, are also relevant, where an individual's prosocial behaviour can be understood as CSR in practice (Hannah et al 2011;van Aaken et al 2013). Prosocial behaviour is understood as voluntary behaviour enacted with the intention of benefiting others (Mikulincer and Shaver 2010, p. 4) and antisocial behaviour as behaviours that have hurtful effects on others (Eisenberg 2010, p. 142).…”
Section: The Motivating Roles Of Personal Values and Reflexivity In Pmentioning
confidence: 99%
“…However, one commonality in notions of leadership is that they encompass a perspective on 'the other', whether this is in terms of employee followership, or, a wider stakeholder perspective. Indeed, for the purposes of our micro-and meso-levels of analysis of CSR leadership, the psychological concepts of prosocial (Penner et al 2005) and, conversely, antisocial behaviour, are also relevant, where an individual's prosocial behaviour can be understood as CSR in practice (Hannah et al 2011;van Aaken et al 2013). Prosocial behaviour is understood as voluntary behaviour enacted with the intention of benefiting others (Mikulincer and Shaver 2010, p. 4) and antisocial behaviour as behaviours that have hurtful effects on others (Eisenberg 2010, p. 142).…”
Section: The Motivating Roles Of Personal Values and Reflexivity In Pmentioning
confidence: 99%
“…One possible explanation for these mixed results is that there are other conditional or mitigating variables that explain the effects of abusive supervision on moral courage. For example, as explained by Hannah et al (2011) In terms of spousal undermining, in Study 1 and Study 2, there was no significant direct effect of moral courage on spousal undermining and no significant indirect effect of abusive supervision on spousal undermining through moral courage. In addition, the moderating effect of family role quality on the relationship with spousal undermining was not significant in both studies.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…According to Bandura (2002), moral agency is a meta-construct that relates to our perceived capacity for moral reasoning and moral courage is defined as a necessity for individuals to resist the temptation to behave unethically when facing a potential threat or risk. Moral courage has been operationalized as a dynamic rather than static human phenomenon and as such it has been argued that moral courage can be malleable and subject to contextual influences such as leadership (Hannah, Avolio, & Walumbwa, 2011). Moral courage can also be considered unique in comparison to conceptually similar constructs such as voice behavior.…”
Section: Moral Courage As a Mediatormentioning
confidence: 99%
“…Two of these studies focused on both situational as well as individual difference moderators (Olsen, Eid & Johnsen, 2006;Yu, 2013), and another study combined situational moderators with individual's personal cognitive abilities (Williams, 2010). These studies suggest leadership (i.e., role models and examples) and hierarchy have a great influence on individual moral behavior (Bartone, 2010;Hannah et al, 2011;Olsen et al, 2006;Reger et al, 2008;Schaubroeck, 2012;Williams, 2010;Yu, 2013). For example, Hannah et al (2013) showed that there is a relationship between the presence of abusive supervision and higher rates of unethical acts towards the local population.…”
Section: 31mentioning
confidence: 99%
“…The majority of the quantitative studies (N = 12) used surveys (self-reports). Five studies used an experimental design, such as peerratings (Hannah et al, 2011) or a pre-post test design (N = 4). In these pre-post test design studies, respondents were asked to fill out surveys before and after training in ethical decision-making (Seiler et al, 2011;Warner, et al, 2011).…”
Section: 32mentioning
confidence: 99%